Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan : The Influence of Organizational Culture and Work Environment on Employee Job Satisfaction - Sheren Pricillia; Rosmita Rosmita (CV Warnak Johanna Nusantara, 2026)
Abstracts - This study aims to determine the influence of organizational culture and work environment on employee job satisfaction. A good organizational culture can shape the company's image and become a guideline for employee behavior. Meanwhile, the physical and non-physical work environment also affects job satisfaction, which ultimately has an impact on employee work results. This study was conducted at the Legal, Cooperation, and Public Relations Bureau of the National Archives of the Republic of Indonesia with a quantitative approach. A sample of 40 employees was obtained through questionnaires. The results of the t-test showed that organizational culture had a significant effect on job satisfaction (t count = 2.366> 2.026; sig. = 0.023 <0.05), and the work environment also had a significant effect (t count = 3.863> 2.026; sig. <0.05). Simultaneously, organizational culture and work environment affected employee job satisfaction (F count = 21.599> 3.24; sig. <0.001). Thus, both variables contributed significantly to increasing employe job satisfaction. Keywords: Organizational Culture, Work Environment, Employee Job Satisfaction.